ASEAN- Australia Trade Relations by Stages of Processing: Comparative Research - Phuong Ha Nguyen; Long Mong Hoang; Dung Duy Nguyen (Diponegoro University, 2020)
ASEAN and Australia became the dialogue partner in 1974. Over 46 years of cooperation and development, ASEAN- Australia relations have achieved many good results, especially in recent years when two sides participate in several free trade agreements (FTAs) at bilateral levels and multilateral levels. In 2014, Australia and ASEAN formally became strategic partners, recognizing the importance of the relationship in building mutual benefits. Participation in FTAs and relationship upgrading has helped bilateral trade growth. In 2018-2019, Australia was the seventh-largest trading partner of ASEAN and ASEAN was one of Australia's top three trading partner, however, the two sides face many challenges such as the difficulties after the global crisis since 2009, the